Review of sustainable Paediatric Cardiac Surgery Program based on Humanitarian Principles at Govt. Medical College, Goa - Kolwalkar, Jagannath; Agarwal, Ravi; Borkar, Shirish; Sunil, Vidya Sagar; Vijay, Madhan (Journal of Humanitarian Cardiovascular Medicine, 2022)
Introduction: Paediatric cardiac surgery and paediatric cardiology set-up is an arduous task, in developing countries, like India (4). Access to advanced cardiac care is unavailable in majority of developing countries (5). Due to high fertility rates in India, the annual estimate of CHD is approximately 150,000–200,000 children per year (6, 10). Of these, approximately a third to a quarter (∼50,000) would need early intervention to survive the first year of life (7, 10). Goa is a small state of India situated along the western coast of Indian peninsula. Goa medical college (GMC) is the only tertiary level institute, providing medical facilities in the state. There were no cardiology or cardiac surgical facilities available at GMC, prior to 2014. The cardiac surgical unit at Goa Medical College was started in April 2014. It provides cardiac surgical services absolutely free of cost to all the citizens of the state. Initially only adult cardiac surgical cases were being performed, but from September 2014, we initiated the paediatric cardiac surgical program, for which we availed the facility of a paediatric cardiac surgeon. Materials and Methods: From 26th Sep 2014 to 11th Jan 2020, we operated a total of 90 cases, during 18 visits of the visiting paediatric cardiac surgeon, who operated an average of 5 cases per visit. Mean age of operated children was 3.2 years. We operated 34 cases of VSD’s, 26 cases of TOF, 8 cases of Tricuspid atresia, 9 cases of ASD, 3 cases of MV repair, 1 case of ASD+PS, 5 cases of TAPVC, 3 PA banding & PDA ligation and one permanent pacemaker implantation. Patients were managed initially in a 5 bedded ICU and after extubation were shifted to a step-down ICU for further recovery. Results: The average duration of ventilation was 36hrs and average length of ICU stay was 5 days. Mean CPB time was 92.46 mins and mean aortic cross clamp time was 59.5 mins. Overall mortality was 5.55%. One patient underwent a redo MV repair, as there was moderate residual MR in post operative period. Conclusion: This model of cardiac surgical program has worked well for the state of Goa and has benefitted lot of people from within the state as well as neighbouring states, where easy and affordable access to cardiac surgical facilities are missing. It has produced excellent outcomes for adult cardiac surgery and has encouraged us to extend the facility to paediatric population. Gradually, our local team is getting confident to do these paediatric cases. Keywords: Congenital heart disease, India, Goa medical college (GMC), Paediatric cardiac surgical care.